1995
DOI: 10.1093/ajcn/61.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron supplementation on blood and urinary calcium, magnesium, and phosphorus, and urinary boron in athletic and sedentary women

Abstract: It has been reported that boron may be beneficial for optimal calcium metabolism and, thus, optimal bone metabolism. Therefore, we designed a study to determine the effects of boron supplementation on blood and urinary minerals in athletic subjects and sedentary control subjects consuming self-selected typical Western diets. Serum phosphorus concentrations were lower in boron-supplemented subjects than in placebo-supplemented subjects. Compared with all other subjects, serum magnesium concentrations were great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…It is reported that dietary boron influences the activity of several micronutrients, including calcium, magnesium, and vitamin D, and boron supplementation in rats and chicks has been shown to increase bone strength [14]. In athletic subjects boron supplementation modestly affected mineral status, and exercise modified the effects of boron supplementation on serum minerals [15]. However, it was also found that 3 mg boron/d for 10 months altered serum mineral levels but did not affect circulating hormones [16].…”
Section: Variablementioning
confidence: 99%
“…It is reported that dietary boron influences the activity of several micronutrients, including calcium, magnesium, and vitamin D, and boron supplementation in rats and chicks has been shown to increase bone strength [14]. In athletic subjects boron supplementation modestly affected mineral status, and exercise modified the effects of boron supplementation on serum minerals [15]. However, it was also found that 3 mg boron/d for 10 months altered serum mineral levels but did not affect circulating hormones [16].…”
Section: Variablementioning
confidence: 99%
“…Its function with regards to nutrition for skeletal structure was proposed in a study by Hunt and Nielsen [7], which reported that supplementation of boron enhanced growth and strengthened skeletal structure in chickens with vitamin D deficiency. Particularly, through experiments on animals [8][9][10][11][12] and humans [13][14][15][16], boron seems to interact with bone metabolism, especially with calcium, magnesium, and vitamin D, to serve an important role in structure and mineral increase of bones.…”
mentioning
confidence: 99%
“…A 10-month boron supplementation study in young female athletes,19 versus sedentary women, produced a modest effect on mineral status. This included a decrease in serum phosphorus and increased urinary calcium excretion which was greater in athletes than in controls.…”
Section: Boronmentioning
confidence: 98%